A Comprehensive Monitoring Study on Electrocardiographic Assessments and Cardiac Events After Fingolimod First Dose—Possible Predictors of Cardiac Outcomes - Limmroth, Volker; Ziemssen, Tjalf; Kleiter, Ingo; Wagner, Bert; Schmidt, Stephan; Lassek, Christoph; Baier-Ebert, Monika; Wendt, Guillaume; Dechend, Ralf; Haverkamp, Wilhelm (Frontiers in Neurology, 2020)
First dose observation for cardiac effects is required for fingolimod. Previous results in patients with relapsing remitting multiple sclerosis (RRMS) suggest that transient bradycardia and conduction abnormalities during the observation phase are rare, benign and reversible. Prior analyses corroborate these findings. The present large scale dataset allows subgroup analyses for differences in the incidence of cardiac findings depending on patient characteristics. START was an open-label, multi-center study that enrolled 6,998 RRMS patients. Primary endpoints were incidence of bradycardia (heart rate < 45 bpm) and second-/third-degree atrioventricular (AV) block during treatment initiation. Subgroup analyses were performed according to age, gender, body mass index (BMI), baseline expanded disability status scale (EDSS) and concomitant medication to determine the impact of these variables on cardiac outcomes parameters. 63 patients (0.9%) developed bradycardia (< 45 bpm), 120 patients (1.7%) had a second-degree Mobitz I (Wenkebach) block and/or 2:1 AV block. One case of an asymptomatic third-degree AV block occurred. No Mobitz II AV block was observed. After one week, no second-/third-degree AV block was observed. The incidence of second- or third-degree AV blocks was significantly higher in older patients (≥50 years; p=0.014 vs. patients 35 - 49 years). Second- or third-degree AV blocks were more frequent in females (87.5% of all patients with a second- or third-degree AV block; p<0.001), while bradycardia occurred more often in males (58.7% of all bradycardia events; p<0.001). Furthermore, patients with a BMI below 25 had a higher incidence of second- or third-degree AV block. In summary, transient bradycardia and AV conduction abnormalities after the first dose of fingolimod were rare and asymptomatic. When compared to females, male patients might have a higher risk for bradycardia during treatment initiation, presumably due to a lower resting heart rate. Furthermore, a low heart rate before treatment initiation, low body weight or low BMI possibly increases the risk for bradycardia. Second- or third-degree AV blocks were more frequent in females, older patients and patients with a low BMI. Nevertheless, these cardiac events remained rare and benign, confirming the favorable cardiac safety profile of fingolimod upon treatment initiation in MS patients without cardiovascular comorbidities.